2014
DOI: 10.1021/am501491u
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Switchable Copper(I) Metallogel: A Metal–Organic Material for Selective and Naked-Eye Sensing of Picric Acid

Abstract: Thiourea (TU), a commercially available laboratory chemical, has been discovered to introduce metallogelation when reacted with copper(II) chloride in aqueous medium. The chemistry involves the reduction of Cu(II) to Cu(I) with concomitant oxidation of thiourea to dithiobisformamidinium dichloride. The gel formation is triggered through metal-ligand complexation, i.e., Cu(I)-TU coordination and extensive hydrogen bonding interactions involving thiourea, the disulfide product, water, and chloride ions. Entangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 74 publications
1
101
0
Order By: Relevance
“…43,44 Our previous study has revealed that aqueous solution of Cu 2+ and thiourea (TU) proceeds through spontaneous one electron transfer protocol involving TU and Cu 2+ which results in Cu(I) species and oxidized form of TU. 39 The presence of Cl -and water molecules in the solution are very important as they participate in weak force interaction (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Our previous study has revealed that aqueous solution of Cu 2+ and thiourea (TU) proceeds through spontaneous one electron transfer protocol involving TU and Cu 2+ which results in Cu(I) species and oxidized form of TU. 39 The presence of Cl -and water molecules in the solution are very important as they participate in weak force interaction (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that TU reduces Cu 2+ to Cu + through one electron transfer process and itself transforms into α,α′-dithiobisformidinium dichloride. 39,[47][48][49] Related crystal structure study discloses the formation of 'CuS 4 ' unit where Cu + centre experiences tetrahedral geometry through sulfur donors of TU and the oxidized dithio product. 39,50 Here it is important to note that each 'CuS 4 ' motif held together through sharing dithio product and also with extended hydrogen bonding.…”
Section: Mechanistic Insight Of Go-gel Formation and Its Transformatimentioning
confidence: 98%
See 1 more Smart Citation
“…The fluorescence quenching of R by TNP is due to an adduct formed between these components through the interaction of the phenolate anion of TNP with the protonated amine center in R that prevents the ICT 20. 24, 54…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity of copper(II) chloride salts over other copper(II) salts in metallogel formation have been reported 51 . Recently, the selectivity of copper(II) chloride and bromide over perchlorate, nitrate, sulphate, and acetate anions was reported 52 . These studies reveal the importance of metal salts specifically copper(II) salts in metallogel formation.…”
Section: Gelation Studiesmentioning
confidence: 99%